Legality Of Land Certificate Issued By Village Head As The Basis For Land Sale And Purchase Transaction - Bima Bagaskara, Arga Nanda (International Significance of Notary, 2023)
Abstract : The village head  is the highest stakeholder in the  village community  where the authority  to decide a   community problem is in  the hands  of the village head. One of  these authorities is to resolve land allergy   problems  arising from  disputes, overlapping  ownership or other  problems arising from  misunderstandings The community in understanding the land problem.  This research has 2 (two)  problem formulations, namely (1) Can the   deed under  hand be used as the basis for issuing a certificate? (2) What is the  basis for a land certificate to  have legal force for the  landowner? The type of research  used in this  study is normative  research  , this   research uses a  statutory approach (statute approach) and   a comparative approach approach (comparative approach).  The results  of  this study are the  legal basis for the authority of the   village head in issuing  land certificates  and fungsi  land certificates as evidence of   guidance legal ownership of land.Keywords:  village head, land certificate, land issue.